2013
DOI: 10.1089/biores.2013.0004
|View full text |Cite
|
Sign up to set email alerts
|

Low Oxygen Tension Enhances Proliferation and Maintains Stemness of Adipose Tissue–Derived Stromal Cells

Abstract: Recent evidence indicates that low oxygen tension or hypoxia alters the characteristics of stem cells. The actions of hypoxia are mediated through the hypoxia-inducible factor, a critical mediator of the cellular response to hypoxia. Adipose tissue–derived stromal cells (ASCs) are one of the most promising cell sources for tissue engineering applications. This study investigated the effect of hypoxia on ASCs in terms of the ability to proliferate and differentiate. ASCs were extracted from mice and maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
6
45
2
Order By: Relevance
“…We have shown that the permanent expansion of ASCs at 5% O 2 lowered the cellular ATP level in these cells, diminishing mitochondrial ATP production and stimulating glycolytic ATP production compared to ASCs at standard 20% O 2 [Buravkova et al, 2013]. These data have been confirmed by others [Yamamoto et al, 2013;Choi et al, 2014;Fotia et al, 2014]. The up-regulation of key 'stemness' genes (Oct3/4, Sox2 and Nanog) in ASCs under tissue-related O 2 was demonstrated [Fotia et al, 2014], indicating that in such conditions ASCs possess the phenotype of uncommitted progenitor cells, which is correlated with less pronounced osteo-and adipogenic induction under low O 2 , as mentioned above [Yamamoto et al, 2013;Fotia et al, 2014].…”
Section: Introductionsupporting
confidence: 81%
“…We have shown that the permanent expansion of ASCs at 5% O 2 lowered the cellular ATP level in these cells, diminishing mitochondrial ATP production and stimulating glycolytic ATP production compared to ASCs at standard 20% O 2 [Buravkova et al, 2013]. These data have been confirmed by others [Yamamoto et al, 2013;Choi et al, 2014;Fotia et al, 2014]. The up-regulation of key 'stemness' genes (Oct3/4, Sox2 and Nanog) in ASCs under tissue-related O 2 was demonstrated [Fotia et al, 2014], indicating that in such conditions ASCs possess the phenotype of uncommitted progenitor cells, which is correlated with less pronounced osteo-and adipogenic induction under low O 2 , as mentioned above [Yamamoto et al, 2013;Fotia et al, 2014].…”
Section: Introductionsupporting
confidence: 81%
“…The avascularity of the cartilage tissue provides a low oxygen environment for the chondrocytes, whereas oxygen measurements of tissues known to harbor stem cells revealed lower oxygen tension to maintain the stemness of the niche. [38][39][40] In our experiments, we observed an increased expression of HIF1A mRNA levels even in normoxic conditions at early time points in AMSCs. The main regulation of HIF1A occurs at the level of protein stability, and its protein levels are strongly stimulated by low oxygen conditions.…”
Section: Discussionsupporting
confidence: 63%
“…Densitometry analysis of PCR amplified cDNA of osterix from two groups revealed marginally lower expression of this osteogenic marker gene in induced hypoxic culture [7,31]. Similar observation has been recently reported in case of Adipose Stem Cells, where hypoxia was found to inhibit osteogenic differentiation [32,33]. Similarly, Chondrocytes differentiation was confirmed by Alcian blue staining and RT-PCR for Collagen-II.…”
Section: Effect Of Hypoxia On Stemness and Differentiation Of Dental supporting
confidence: 84%